Systolic Blood Pressure Within 24 Hours After Thrombectomy for Acute Ischemic Stroke Correlates With Outcome. Issue 5 (May 2017) - Mistry, Eva A.; Mistry, Akshitkumar M.; Nakawah, Mohammad Obadah; Khattar, Nicolas K.; Fortuny, Enzo M.; Cruz, Aurora S.; Froehler, Michael T.; Chitale, Rohan V.; James, Robert F.; Fusco, Matthew R.; Volpi, John J.
Abstract : Background: Current guidelines suggest treating blood pressure above 180/105 mm Hg during the first 24 hours in patients with acute ischemic stroke undergoing any form of recanalization therapy. Currently, no studies exist to guide blood pressure management in patients with stroke treated specifically with mechanical thrombectomy. We aimed to determine the association between blood pressure parameters within the first 24 hours after mechanical thrombectomy and patient outcomes. Methods and Results: We retrospectively studied a consecutive sample of adult patients who underwent mechanical thrombectomy for acute ischemic stroke of the anterior cerebral circulation at 3 institutions from March 2015 to October 2016. We collected the values of maximum, minimum, and average values of systolic blood pressure, diastolic blood pressure, and mean arterial pressures in the first 24 hours after mechanical thrombectomy. Primary and secondary outcomes were patients' functional status at 90 days measured on the modified Rankin scale and the incidence and severity of intracranial hemorrhages within 48 hours. Associations were explored using an ordered multivariable logistic regression analyses. A total of 228 patients were included (mean age 65.8±14.3; 104 males, 45.6%). Maximum systolic blood pressure independently correlated with a worse 90‐day modified Rankin scale and hemorrhagic complications within 48 hours (adjusted odds ratio=1.02 [1.01–1.03], P =0.004; 1.02 [1.01–1.04], P =0.002; respectively) in multivariable analyses, after adjusting for several possible confounders. Conclusions: Higher peak values of systolic blood pressure independently correlated with worse 90‐day modified Rankin scale and a higher rate of hemorrhagic complications. Further prospective studies are warranted to identify whether systolic blood pressure is a therapeutic target to improve outcomes.